THE QUALITY OF BROILER CARCASSES SOLD IN TRADITIONAL MARKETS OF SOUTH DENPASAR SUBDISTRICT - Wulandari, Suci; Swacita, Ida Bagus Ngurah; Rudyanto, Mas Djoko (Buletin Veteriner Udayana, 2020)
This study aims to evaluate the quality of broiler carcasses that are sold in traditional markets of South Denpasar District . Sampling was conducted in four traditional markets and each market was picked up by three sellers with six repetitions. The parameters observed included water holding capacity (WHC), pH value, and cooking loss. The measurement data were analyzed by ANOVA test and if there was a significant difference (P <0.05) then will be continued with Duncan's New Multiple Range Test. The results showed that pH and Water Holding Capacity (WHC) test of broiler meat in all four markets in South Denpasar district was not significantly different (P>0,05). Meanwhile, the cooking loss showed significantly different results (P <0.05) in each market. Based on the research, it can be concluded that the quality of broiler meat sold in the traditional market of South Denpasar District is still good and feasible to be consumed.